India and World War I
1 online resource
Keywords: "World War I directly and indirectly caused events and social and political trends which defined the history of the world for the rest of the century, including the Russian Revolution and the rise of communism to the Great Crash of 1929 which lead to the Great Depression and the rise of Hitler and Nazi Germany. It marked a turning point in world history as the end of the historical era of European dominance and the ushering in of a period which accelerated demands for freedom and autonomy in colonial settings. India played a significant role in the war and in the Allied victory on the battlefield. This book explores Indias involvement in the Great War and the way the war impacted upon the country from a variety of different viewpoints including case studies focusing on key individuals who played vital roles in the war. The long and short term impacts of the war on different locations in India are also explored in the chapters which offer an analysis of the importance of the war on India while commemorating the sacrifices which were made. A new, innovative and multidisciplinary examination of India and World War I, this book presents a select number of case studies showing the intimate relationship of the global war and its social, political and economic impacts on the Indian subcontinent. It will be of interest to academics in the field of War Studies, Colonial and Imperial History and South Asian and Modern Indian History. "--Provided by publisher.